The Impact of Corporate Social Responsibility on Organizational Commitment: Exploring Multiple Mediation Mechanisms - Farooq, Omer (Journal of business ethics, 2014)
Unlike previous studies that examine the direct effect of employees’ perceived corporate social responsibility (CSR) on affective organizational commitment (AOC), this article examines a mediated link through organizational trust and organizational identification. Social exchange and social identity theory provide the foundation for predictions that the primary outcomes of CSR initiatives are organizational trust and organizational identification, which in turn affect AOC. The test of the research model relies on data collected from 378 employees of local and multinational companies in South Asia, as well as structural equation modeling to test the postulated relationships. Both organizational trust and organizational identification fully mediate the CSR–AOC link. However, the identification mechanism is significantly stronger than the trust mechanism in terms of building AOC from CSR. Out of four CSR components, CSR toward employees is the strongest predictor of employees’ trust, identification, and AOC, followed by CSR toward community, whereas CSR toward the environment has no effect. Finally, CSR toward community and employees are more associated with social exchange, whereas CSR toward consumers relates more to the social identity process.